Application of the hierarchical analysis in the selection of lands for the installation of a solid waste sorting center in São Gonçalo do Rio Abaixo (Minas Gerais) (Research, Society and Development, 2020)
The management of solid waste comprises the stages of collection, storage, treatment, transportation and final disposal of these materials, aiming to ensure the preservation of the environment and public health. In this sense, this work aimed to identify areas for the implementation of a solid waste sorting center in the city of São Gonçalo do Rio Abaixo (MG), using as a support the Analytical Hierarchical Process (AHP) method, besides characterizing the generation and disposal of solid waste in the city. The methodology used was quali-quantitative, through documentary and field research, with satellite images and documents related to municipal legislation being analyzed, such as the master plan. It was noted that a projection involving the generation of solid waste between 2017 and 2028 indicates a growth of approximately 10% of these, thus, the useful life of the landfill in operation will not be enough. Regarding the selection of the area for the installation of a sorting center, it was found that the best alternative is area 3, located in Perobas, which, although not the largest and having nearby vegetation, has access to the road system and is not located. close to a water course, a criterion considered of most importance in this analysis. Finally, it is emphasized that the minimization involving the generation of waste and the proper treatment of these are items that contribute to the population's quality of life and the reduction of negative environmental impacts associated with the incorrect disposal of these materials.